Protein Traffic to the Plasmodium falciparum Apicoplast: Evidence for a Sorting Branch Point at the Golgi. (15th October 2014) - Heiny, Sabrina R.; Pautz, Sabine; Recker, Mario; Przyborski, Jude M.
<x xml:space="preserve">Abstract</x> Plasmodium falciparum, similar to many other apicomplexan parasites, contains an apicoplast, a plastid organelle of secondary endosymbiotic origin. Nuclear‐encoded proteins are posttranslationally transported to the apicoplast via the endoplasmic reticulum. However, it has long been a matter of contention if the Golgi also plays a role in this process. In this study, we show that trafficking to the apicoplast occurs via the Golgi as an intermediate compartment. Our data suggest that the Plasmodium Golgi has an important function as a protein sorting compartment.